THE ROLE OF BRAND AWARENESS IN MEDIATING THE EFFECT OF SOCIAL MEDIA MARKETING ON PURCHASE INTENTION AT FORE COFFEE RENON DENPASAR - I Gede Krisna Wiradinatha; I Gst. A. Kt. Gd. Suasana (CV. Adiba Aisha Amira, 2026)
Competition within the coffee shop industry in Denpasar City has become increasingly intense, with approximately 550 coffee shops currently in operation. This competition is also reflected in the dominance of major brands such as Kopi Kenangan, Fore Coffee, and Janji Jiwa based on the number of outlets. In Denpasar, Fore Coffee ranks below its primary competitors, highlighting the need for more effective marketing strategies, particularly at the Fore Coffee Renon Denpasar branch, to enhance competitiveness and attract consumers. This study was conducted in Denpasar City using a sample of 120 respondents selected through a purposive sampling technique. Data were collected through an online questionnaire and analysed using path analysis and the Sobel test with the assistance of SPSS version 27. The results indicate that all hypotheses were supported. Social media marketing has a positive and significant effect on both purchase intention and brand awareness. Brand awareness also has a positive and significant effect on purchase intention and partially mediates the relationship between social media marketing and purchase intention. The theoretical implication of this study enriches the hierarchy of effect model within the context of the Fore Coffee Renon Denpasar branch. Practically, the findings emphasise the importance of implementing effective social media marketing strategies to enhance brand awareness and encourage consumers' purchase intention.